ANTIBACTERIAL EFFICACY OF SILVER AND COPPER NANOPARTICLES AGAINST E. COLI IN CATHETER-ASSOCIATED URINARY TRACT INFECTIONS - VAISHNAVI K. PIDADI,; VAISHALI U. THOOL, (The Bioscan, 2025)
The rise of antibiotic-resistant E. coli in catheter-associated urinary tract infections necessitates the exploration of new treatment strategies. This study examined the antibacterial efficacy of silver and copper oxide nanoparticles against E. coli isolates obtained from CAUTIs. Antibiotic susceptibility testing demonstrated notable resistance to frequently prescribed antibiotics, underscoring the critical need for alternative treatment modalities. Silver nanoparticles, measuring approximately 6.66 nm, demonstrated potent antibacterial activity, producing inhibition zones ranging from 11 mm to 19 mm at concentrations of 1 mg/ml and 5 mg/ml, respectively. Conversely, copper oxide nanoparticles, with an average size of 39.64 nm, exhibited moderate antibacterial effects, especially at higher concentrations. The superior efficacy of AgNPs is attributed to their smaller size, larger surface area-to-volume ratio, and increased reactivity. Additionally, scanning electron microscopy and energy-dispersive X-ray spectroscopy confirmed the morphology and elemental composition of the nanoparticles. These findings indicate that AgNPs have significant potential as an alternative treatment for E. coli-induced CAUTIs with increasing antibiotic resistance. Nevertheless, further research is essential to refine nanoparticle formulations and investigate their genetic and molecular interactions, emphasizing the continuous effort required from the scientific community in this area.